Coordination Behaviour of Some Aryl and Thiazolyl Hydrazones towards Dioxomolybdenum(VI) - Srivastava, A.K.; Singh, A.K. (Asian Journal of Chemistry, 2010)
Aryl and thiazolyl hydrazones were synthesized by coupling reaction of diazotized solution of aniline, o-toluidine, 2-aminobenzothiazole and its methyl derivative with acetoacetanilide. These compounds were used as ligands and their dioxomolybdenum (VI) complexes were synthesised. On the basis of elemental analysis their compositions were proposed as MoO2L·H2O, where L = thiazolylhydrazone and MoO2L·2H2O, where L = arylhydrazones. All the complexes were found to be diamagnetic and nonelectrolytic in nature. The IR spectral studies revealed that after enolisation and subsequent deprotonation the thiazolyl hydrazones behaved as NOS donor dinegative ligand whereas aryl hydarazones behaved as NO donor dinegative ligands towards MoO2+2 ion. All the complexes were cis-dioxo complexes. Pseudo octahedral geometry was tentatively proposed for all the synthesised complexes.